2020
DOI: 10.1108/wje-08-2019-0217
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance of a double-pass solar air heater (SAH) with ribbed absorber surface – an experimental study

Abstract: Purpose Use of packed beds, enhanced tubes, nano-fluids and artificial ribs are few passive techniques to increase heat transfer in solar air heaters (SAHs). Artificial ribs attached to the absorber plate of the SAH will enhance the turbulence near the plate. Experimental analyses are conducted to find the thermal performance of SAH with ribs of regular geometries including rectangular, semi-circular and triangular in cross section. This paper aims to present the improvement in thermal performance of SAH with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Ribs on absorber plate creates more turbulence near the plate and hence local heat transfer coefficients increases with simultaneous increase in efficiency of SAH. Gupta and Garg, 10 Esen, 11 El-Sebaii et al, 12,13 and Nandkishor and Mohan 14 verify this fact experimentally.…”
Section: Introductionmentioning
confidence: 78%
“…Ribs on absorber plate creates more turbulence near the plate and hence local heat transfer coefficients increases with simultaneous increase in efficiency of SAH. Gupta and Garg, 10 Esen, 11 El-Sebaii et al, 12,13 and Nandkishor and Mohan 14 verify this fact experimentally.…”
Section: Introductionmentioning
confidence: 78%
“…Artificial roughness of various forms and geometrical shapes investigated by different researchers is reported in the literature. The use of rib roughness in numerous shapes and geometries, such as square, 88,90,[103][104][105] triangular, 92,95,106,107 rectangular, 106,107 inclined, 93 V-shaped, 89,108 W-shaped, 94 discrete, 93,94,109 chamfered, 88 wedge shaped, 107 arc shaped, 97,106,110,111 L shaped, 96 U shaped, 91 porous rib type roughness, 112 and pentagonal ribs 98 result a better performance compared to conventional-type solar air collector. Many of the investigators reported considerable enhancement in heat transfer with less penalty of friction by the application of…”
Section: Ribs and Groovesmentioning
confidence: 99%
“…Geometry of different rib profiles 106 medium. 121,124,126 Therefore, it is concluded from most of the studies that incorporating paraffin wax as heat storage material reduced the discrepancy between the energy supply and demand and enhancement in energy efficiency by providing thermal stability.…”
Section: F I G U R Ementioning
confidence: 99%
“…It has been determined that surface roughness plays a significant role in heat transfer and friction behaviors in solar air heater (SAH) ducts. Various approaches have explored the use of surface roughness created by repeating ribs in the same pattern on the SAH duct's surface as an effective means of increasing system efficiency 15,21 . Implementing fins or ribs on the surface disrupts the formation of a laminar sub‐layer, which contributes to overall thermal losses and reduces efficiency 22–28 …”
Section: Introductionmentioning
confidence: 99%
“…Various approaches have explored the use of surface roughness created by repeating ribs in the same pattern on the SAH duct's surface as an effective means of increasing system efficiency. 15,21 Implementing fins or ribs on the surface disrupts the formation of a laminar sub-layer, which contributes to overall thermal losses and reduces efficiency. [22][23][24][25][26][27][28] Although SAHs suffer from poor thermal efficiency due to heat loss from various parts and low heat transfer coefficient, they remain the most cost-effective system of converting solar energy into heat.…”
mentioning
confidence: 99%